Machine Learning in Unmanned Systems for Chemical Synthesis - Guoqiang Wang; Xuefei Wu; Bo Xin; Xu Gu; Gaobo Wang; Yong Zhang; Jiabao Zhao; Xu Cheng; Chunlin Chen; Jing Ma (Molecules, 2023)
Chemical synthesis is state-of-the-art, and, therefore, it is generally based on chemical intuition or experience of researchers. The upgraded paradigm that incorporates automation technology and machine learning (ML) algorithms has recently been merged into almost every subdiscipline of chemical science, from material discovery to catalyst/reaction design to synthetic route planning, which often takes the form of unmanned systems. The ML algorithms and their application scenarios in unmanned systems for chemical synthesis were presented. The prospects for strengthening the connection between reaction pathway exploration and the existing automatic reaction platform and solutions for improving autonomation through information extraction, robots, computer vision, and intelligent scheduling were proposed.